2007
DOI: 10.1029/2007gl031813
|View full text |Cite
|
Sign up to set email alerts
|

Explaining soil moisture variability as a function of mean soil moisture: A stochastic unsaturated flow perspective

Abstract: Understanding soil moisture variability and its relationship with water content at various scales is a key issue in hydrological research. In this paper we predict this relationship by stochastic analysis of the unsaturated Brooks‐Corey flow in heterogeneous soils. Using sensitivity analysis, we show that parameters of the moisture retention characteristic and their spatial variability determine to a large extent the shape of the soil moisture variance‐mean water content function. We demonstrate that soil hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
174
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(190 citation statements)
references
References 20 publications
16
174
0
Order By: Relevance
“…The trend of the CV approximates a decreasing power function, with a high coefficient of determination (R 2 > 0.87). Our results agree with the findings reported in [60]. However, it can be observed that, above values of 0. , the CV tends to vary linearly with the mean of the soil moisture, as reported also in [67,68].…”
Section: Soil Moisture Spatial Variabilitysupporting
confidence: 40%
See 1 more Smart Citation
“…The trend of the CV approximates a decreasing power function, with a high coefficient of determination (R 2 > 0.87). Our results agree with the findings reported in [60]. However, it can be observed that, above values of 0. , the CV tends to vary linearly with the mean of the soil moisture, as reported also in [67,68].…”
Section: Soil Moisture Spatial Variabilitysupporting
confidence: 40%
“…Heterogeneity of terrain, vegetation cover and topography can make the soil moisture extremely variable even over small distances [60], a variability that the coarse spatial resolution of the ECV SM product may mask. Previous studies [61][62][63] used soil moisture measurements recorded in several in situ stations aiming at the understanding of soil moisture variability over relatively small distances.…”
Section: Analysis Of Sm Spatial Variabilitymentioning
confidence: 99%
“…The spatiotemporal correlations between soil moisture variability and mean moisture content have been examined extensively in various environmental contexts. However, there is no consensus to the results (Vereecken et al 2007). Some studies have found increases in the standard deviation (SD) of soil moisture with reductions in the mean moisture content (Brocca et al 2007;Hupet and Vanclooster 2002), while others have found the opposite (Famiglietti et al 1998;Martinez-Fernandez and Ceballos 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Soil water content (SWC) of surface soils exerts a major influence on a series of hydrological processes such as runoff and infiltration (Famiglietti et al, 1998;Vereecken et al, 2007;She et al, 2013a). Soil water content in the root zone is, in many cases, linked to vegetative growth (Wang et al, 2012;Ward et al, 2012;Jia and Shao, 2013).…”
Section: Introductionmentioning
confidence: 99%